AB0392 Not Increased Cancer Frequency at Patients with Rheumatoid Arthritis During TNF Inhibitor Treatments: Hur-Bio Real Life Results. (9th June 2015) - Torgutalp, M.; Kilickap, S.; Babaoglu, H.; Karadag, O.; Kilic, L.; Erden, A.; Akdogan, A.; Bilgen, S.A.; Kiraz, S.; Ertenli, I.; Kalyoncu, U.
Abstract : Background: There are still controversial data regarding the development of malignancy after TNF inhibitor (TNFi) therapy. Objectives: The objective of this study was to assess whether TNFi increases the risk of cancer development in Turkish Rheumatoid Arthritis (RA) patients in a single center real life experience Methods: HUR-BIO (Hacettepe University Rheumatology Biologic Registry) is a single center biological registry since 2005 that include 815 RA patients under biological treatments. Overall, 679 of 815 patients were treated with TNFi drugs. Collected data includes demographic data, co-morbidities, smoking, switch ratio, baseline and follow-up disease activity parameters. Malignancy history before TNFi drugs were recorded from local database. After TNFi exposure, malignancy data were obtained from local database, social security administration data and Republic of Turkey Ministry of Health data. Development of cancer was assessed by calculating 100 patient–year exposure. These results are compared with Turkey 2005 Cancer Data and standardized incidence ratio (SIR) were identified (1). SIR was calculated by multiplying the ratio between expected number of cancers and observed number of cancer by 100. Results: The mean age of 679 RA (77.8% women) patients was 50.4 (13.1) years and total duration of TNFi was 1623 patient-years. Initial TNFi were adalimumab 223 (32.8%), etanercept 321 (47.3%), infliximab 115 (16.9%) and golimumab 20 (3.0%). Before TNFi drugs, 2 patients had malignancy history (one breast cancer and one prostate cancer). During follow-up period, 5 additional cancer were obtained (Table 1 ). SIR was calculated as 1.26 in patients with advanced malignancy after anti-TNF drugs (confidence interval could not be obtained because of the small sample size). Conclusions: In this single center real life experience, the incidence of malignancy after TNFi drugs at RA patients probably remains within the confidence interval according to the healthy population. We did not have RA control groups with DMARDs, and this is the limitation of our study. References: Haydaroğlu A et al. Türk Onkoloji Dergisi 2007;22:22-28. Disclosure of Interest: None declared